(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
In this article, the history of the development of status art and its development today, issues such as studying it and teaching status art to the younger generation today, attention to status art and status in Uzbekistan Information about the measures being implemented for the development of art, "Maqom Festival" held in Shahrisabz city.